Wage Gains Associated with Height as a Form of Health Human Capital - Schultz, T. Paul (American Economic Review, 2002)
Height is consulted as a latent indicator of early nutrition and lifetime health status. Height is observed to increase in recent decades in populations where per capita national income has increased and public health activities have grown. Height is determined by genetic make up and realized in part through satisfactory nutrition and health related care and conditions. Alternative instrumental variables (IV) are explored which proxy price and income constraints which are expected to influence the latter reproducible human capital investments in height. I report OLS and IV estimates of the partial effect of height on log hourly wages in recent national surveys from three countries: Ghana, Brazil and the United States. I conclude that the human capital productivity effect of height estimated by parent education IVs in the US and Ghana are many times larger than the OLS estimates, and in Ghana and Brazil the regional price IVs estimates also imply a substantially larger human capital wage effects of height compared with the OLS estimates. The OLS estimates of height effects on wages are dominated by the genetic variation in height, and appear to understate substantially the human capital returns to health and nutrition inputs which increase adult height.